The action of mimetic peptides on connexins protects fibroblasts from the negative effects of ischemia reperfusion - Glass, Beverley J. (2018)
Connexins have been proposed as a target for therapeutic treatment of a variety of conditions. The main approaches have been by antisense or small peptides specific against connexins. Some of these peptides enhance communication while others interfere with connexin binding partners or bind to the intracellular and extracellular loops of connexins. Here, we explored the mechanism of action of a connexin mimetic peptide by evaluating its effect on gap junction channels, connexin protein levels and hemichannel activity in fibroblast cells under normal conditions and following ischemia reperfusion injury which elevates Cx43 levels, increases hemichannel activity and causes cell death. Our results showed that the effects of the mimetic peptide were concentration-dependent. High concentrations (100-300 μM) significantly reduced Cx43 protein levels and GJIC within 2 h, while these effects did not appear until 6 h when using lower concentrations (10-30 μM). Cell death can be reduced when hemichannel opening and GJIC were minimised.